Facilitating regional and remote access to voluntary assisted dying in Western Australia: targeted initiatives during the law-making and implementation stages of reform - Lindy Willmott; Casey Haining; Ben White (James Cook University, 2023)
Australians living in regional and remote communities face several barriers when accessing high quality health care. Voluntary assisted dying (VAD), a new and sensitive end-of-life option, presents a new challenge for residents living in these communities. Western Australia (WA) is the second Australian state to implement VAD laws and, to date, is the jurisdiction with the greatest need to address access inequities in regional and remote communities due to its vast area. This article identifies and explores initiatives introduced by the WA Government to address regional and remote access inequities in each of the two stages of the reform process: the stage of the reform process leading up to passing the law ('law-making stage'), and the stage of the reform process after the law was passed and prior to it commencing operation ('implementation stage'). The analysis reveals that several initiatives were implemented during each of the law-making and implementation stages of reform. Initiatives introduced in the law-making stage through inclusion in the legislation itself included dedicated guiding principles promoting equality of access for regional and remote residents, broadened qualification requirements for medical practitioners who can participate in VAD, allowing nurse practitioner administration, and mandating that statistics relating to regional and remote access are recorded and reported. Other initiatives dedicated to facilitating regional and remote access were not specifically provided for by legislation but were introduced during the implementation stage of the reform process. These include the establishment of a Statewide Care Navigator Service that administers a Regional Access Support Scheme and ensuring that the Statewide Pharmacy Service is accessible to regional and remote residents. Other initiatives intended to facilitate regional and remote access were provided for in legislation but given further content during the implementation stage. These include an access standard (contents determined by the CEO during implementation) and telehealth (supporting guidance around lawful use issued by the WA Government during implementation). This policy report reveals that WA took a considered and targeted focus to address regional and remote access in both the law-making and implementation stages of reform. Given VAD in WA is still in the early stages of its operation, it is too soon to determine how effective these initiatives have been in promoting regional and remote access to VAD in WA. Careful evaluation of these initiatives will be crucial to monitor their effectiveness and to assess whether additional measures are needed. Reflecting on the WA experience will also be valuable for other states as they legalise VAD and develop (and adapt) their own access initiatives.